Potential application of hyperspectral imaging in food grain quality inspection, evaluation and control during bulk storage - Aviara, Ndubisi A.; Liberty, Jacob Tizhe; Olatunbosun, Ojo S.; Shoyombo, Habib A.; Oyeniyi, Samuel K. (Journal of agriculture and food research, 2022)
The presence of impurities in food grains greatly impact their grades and quality as well as their overall acceptance. Additionally, bulk grains storage is subject to deterioration and losses through factors that could be biological (insects, fungi, mites, mould, rodents) or environmental (temperature, moisture and relative humidity). Several techniques ranging from manual methods (human sensory) to microbiological and chemical tests have been employed in carrying out quality assessments to control deterioration in stored bulk grains. However, it is often challenging, time-consuming and expensive to discriminately identify grain contaminants in store using the traditional methods, especially when they are physically and sometimes visually similar. The hyperspectral imaging, an emerging technique that combines the technology of conventional imaging (computer vision), radiometry and spectroscopy to simultaneously obtain both spatial and spectral information from a sample is potentially a viable approach. Studies on the application of this technology to food grain quality inspection during bulk storage appears to be scanty. Herein a comprehensive review on the applicability of hyperspectral imagining for food grain quality assessment is presented and its potential for application in grain quality inspection, evaluation and control during bulk storage is provided. Specifically, the work presents the basic theory and principles of hyperspectral imaging, and its recent uses in quality and safety inspection of agro-food products. It highlights and discusses the potential and possible approaches in the application of the technology for food grains quality inspection, evaluation and control during bulk storage. Particularly, hyperspectral imaging systems utilizing line or area scanning were considered capable and proposed for application in bulk grain storage quality inspection. Existing literature showed that most studies on the application of hyperspectral imaging for grain quality assessment were majorly focused on wheats. Future research should consider other grains. [Display omitted] •Hyperspectral imaging is an emerging method of obtaining spatial and spectral data.•It is potentially a viable approach for food quality investigation.•Its application in grain quality evaluation during bulk storage is discussed.•Line or area scanning is possible approach for achieving the above purpose.